(3COH GdWHjHs - (3ESMGb Hf Ydj GdQgGhjs
(3ChdgG (B:s
(3bGd LGeY gPG GdcJGH heDdag CfG CfGSkG ef GdCWHGA CjgG GdMHjH CSYOc Gddg HHdhZ eWdhHJGc hCYGfc Ydi OQc GdMb Mjf LgdhG CUhd UfGYI GdWH s
(3BNQgG (B:s
(3aUf faSc hLSec Hdhe GdYOd ai GSJYeGd GdCYJOGd ai JcSHc ddeGd hai fabJg ai SGFQ CaYGdc JfL HPdc ef GdBKGe Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B46s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs